Standardisation of foliar spray of boron for correction of brown rot and for increasing yield of cauliflower (Brassica oleracea convar botrytis var botrytis) in Bihar plateau - KOTUR, SHIVAPUTRA C (The Indian Journal of Agricultural Sciences, 2013)
Field experiment was conducted during 1989-92 at Ranchi on a red sandy loam (Ultic Haplustalf) deficient in available boron (0.01 flg/g hot-water soluble (HWS) B] with ’Pusa Snow Ball K-1’ cauliflower. Foliar application of B was as good as soil application @ 1.5 kg B/ha in increasing curd yield, B and Ca content of leaf and Ca : B ratio in leaf-tissue. Reduction of curd-rot was signiticant compared to control but of lower order than that achieved with soil application. Among spray concentrations (0.125 - 4.00 % boric acid) and spray numbers (1- 4, 10 days after transplanting at 15 days interval), the highest curd yield (14.73 tonnes/ha) was obtained at 0.125 % spray concentration while the lowest curd-yield of 6.87 tonnes/ha curd yield was obtained at control. The curd-yield declined at higher spray concentrations due to excess B applied, the lowest being at 4.00% boric acid (12.41 tonnes/ha). Spray concentration above 1.00% and 2 sprays caused irreversible yellowing/scorching, reduction of plant-growth and high residual hot water soluble B in soil (0.95 - 3.90 flg/g). Application of 3 sprays was adequate. Among lower spray concentrations (0.025 - 0.125%) applied in 3 sprays, the curd-yield increased with that of spray concentration (18.32 - 21.81 tonnes/ha) while the curd-rot decreased (51 - 2%). Foliar application of 3 sprays of 0.125% boric acid was optimum for high curd-yield (23.46 tonnes/ha, 76% higher than the control), low curd-rot (5%), negligible residual hot water soluble B in soil (0.11 flg/g) and high net returns per rupee invested (Rs 4.74) corresponding to 23.45 flg/g of B and Ca:B ratio of 678 in leaf-tissue.